Active Engagement, Protective Buffering, and Depressive Symptoms in Young-Midlife Couples Surviving Cancer: The Roles of Age and Sex - Lyons, Karen S.; Gorman, Jessica R.; Larkin, Brandon S.; Duncan, Grace; Hayes-Lattin, Brandon (Frontiers in Psychology, 2022)
Objective Cancer researchers have found midlife couples to have poorer outcomes compared to older couples due to the off-time nature of the illness for them. It is unknown if young couples (aged 18–39), who are under-represented in cancer studies and overlooked for supportive programs, are at further risk. This study explored the moderating roles of survivor age and sex on the associations between active engagement and protective buffering and depressive symptoms in couples surviving cancer. Methods The exploratory study comprised 49 couples (aged 27–58) 1–3 years post-diagnosis. Multilevel modeling was used to explore the moderating roles of survivor age and sex, controlling for interdependent data. Results Approximately, 37% of survivors and 27% of partners met clinical criteria for further assessment of depression, with 50% of couples having at least one member meeting the criteria. Survivors and their partners did not significantly differ on depressive symptoms, active engagement, or protective buffering. Male survivors reported significantly higher levels of active engagement by their partners than female survivors and female survivors reported significantly higher levels of protective buffering by their partners than male survivors. We found some evidence to suggest that survivor age and sex may play moderating roles between active engagement and protective buffering and depressive symptoms. Older partners and female survivors appeared to experience more positive effects from engaging in positive dyadic behaviors than younger partners and male survivors. Conclusion Findings not only confirm the important role of dyadic behaviors for couples surviving cancer together, but also the important roles of survivor age and sex may play in whether such behaviors are associated with lower levels of depressive symptoms. Future research that examines these complex associations over time and across the adult life span in diverse populations is needed.